A systematic review of service models and evidence relating to the clinically operated community-based residential mental health rehabilitation for adults with severe and persisting mental illness in Australia - Parker, Stephen (BMC Psychiatry, 2019)
BACKGROUND: Clinically operated community-based residential rehabilitation units (Community Rehabilitation Units) are resource intensive services supporting a small proportion of the people with severe and persisting mental illness who experience difficulties living in the community. Most consumers who engage with these services will be diagnosed with schizophrenia or a related disorder. This review seeks to: generate a typology of service models, describe the characteristics of the consumers accessing these services, and synthesise available evidence about consumers’ service experiences and outcomes. METHOD: A systematic review was undertaken to identify studies describing Community Rehabilitation Units in Australia, consumer characteristics, and evidence about consumer experiences and outcomes. Search strings were applied to multiple databases; additional records were identified through snowballing. Records presenting unique empirical research were subject to quality appraisal. RESULTS: The typology defined two service types, Community-Based Residential Care (C-BRC), which emerged in the context of de-institutionalisation, and the more recent Transitional Residential Rehabilitation (TRR) approach. Key differentiating features were the focus on transitional care and ‘recovery’ under TRR. Schizophrenia spectrum disorders were the most common primary diagnosis under both service types. TRR consumers were more likely to be male, referred from community settings, and less likely to be subject to involuntary treatment. Regarding outcomes, the limited quantitative evidence (4 records, 2 poor quality) indicated C-BRC was successful in supporting the majority of consumers transferred from long-term inpatient care to remain out of hospital. All qualitative research conducted in C-BRC settings was assessed to be of poor quality (3 records). No methodologically sound quantitative evidence on the outcomes of TRR was identified. Qualitative research undertaken in these settings was of mixed quality (9 records), and the four records exploring consumer perspectives identified them as valuing the service provided. CONCLUSIONS: While there is qualitative evidence to suggest consumers value the support provided by Community Rehabilitation Units, there is an absence of methodologically sound quantitative research about the consumer outcomes achieved by these services. Given the ongoing and increasing investment in these facilities within the Australian context, there is an urgent need for high-quality research examining their efficiency and effectiveness. TRIAL REGISTRATION: PROSPERO (CRD42018097326). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12888-019-2019-5) contains supplementary material, which is available to authorized users.